Perbandingan Pemahaman Konsep Fisika Melalui Strategi Pembelajaran JIGSAW Dan Learning Tournament - Ikbal, Muh Syihab (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This study aims to analyze the differences in students' understanding of physics concepts through the application of jigsaw learning strategies and learning tournaments. The research design used was the matching only post-test group design. The research population was 286 people spread over 9 classes. The research sample amounted to 64 people obtained by using a two-step matching sampling technique and spread evenly in two classes, namely experimental class 1 and experimental class 2. Experimental class 1 was taught by jigsaw learning strategy and experimental class 2 was taught by learning tournament strategy. The instrument used is a concept understanding test instrument. The results of the descriptive analysis showed that the average score of understanding the concepts of students who were taught with the jigsaw strategy was 11.97 and the learning tournament strategy was 10.31. The difference test analysis shows that the arithmetic significance value = 0.01 is smaller than the 0.05 significance level, so it can be concluded that there is a significant difference in understanding physics concepts between students who are taught with the Jigsaw learning strategy and students who are taught with the learning tournament strategy.